2007
DOI: 10.1111/j.1600-6143.2006.01596.x
|View full text |Cite
|
Sign up to set email alerts
|

Selective Use of Older Adults in Right Lobe Living Donor Liver Transplantation

Abstract: Many centers are reluctant to use older donors (>44 years) for adult right-lobe living donor liver transplantation (RLDLT) due to concerns about possible increased morbidity in donors and poorer outcomes in recipients. Since 2000, 130 adult RLDLTs have been performed at our institution. Recipients were divided into those who received a right lobe graft from a donor ≤age 44 (n = 89, 68%; median age 30) and those who received a liver graft from a donor age >44 (n = 41, 32%; mean age 52). The two donor and recipi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 49 publications
(56 reference statements)
1
23
0
Order By: Relevance
“…Our data showed a midway incidence of major donor complications of 12.6% in the range of 2%‐32% reported by other series including those where outcomes were evaluated with a different Clavien grading system, with a rate of ≥3 Clavien complications estimated at approximately 20%‐25% . Nevertheless, data from large Far Eastern centers with the lowest recipient morbidity and best survival rates also report the lowest incidence of donor ≥3 Clavien complications at < 10% .…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Our data showed a midway incidence of major donor complications of 12.6% in the range of 2%‐32% reported by other series including those where outcomes were evaluated with a different Clavien grading system, with a rate of ≥3 Clavien complications estimated at approximately 20%‐25% . Nevertheless, data from large Far Eastern centers with the lowest recipient morbidity and best survival rates also report the lowest incidence of donor ≥3 Clavien complications at < 10% .…”
Section: Discussionsupporting
confidence: 58%
“…Nevertheless, data from large Far Eastern centers with the lowest recipient morbidity and best survival rates also report the lowest incidence of donor ≥3 Clavien complications at < 10% . According to the data reported by the A2ALL study group and the Toronto group, a range from 2% to 5% could be considered the definitive risk of intraoperative aborted living RL donation . Our survey found a lower rate of no‐go hepatectomies with only 1 (1/247, 0.4%) donor procedure being aborted.…”
Section: Discussionmentioning
confidence: 51%
“…It is noteworthy that the large Asian centers with the lowest recipient morbidity and best survival [21,23,24,40] also had the smallest incidence of donor ≥III Clavien complications (4.9–9%) [3740]. Although donor studies by the Toronto group [44] and by the A2ALL consortium [45] were done with the 4-tier system, enough detail was provided to estimate an approximately 20–25% rate of ≥III Clavien complications.…”
Section: Discussionmentioning
confidence: 99%
“…There was a 41% higher risk of graft failure with each 10-year increase in recipient age (P = 0.0008) [14••]; however, the advanced age-related increase was not significant. In fact, two recent studies have reported data suggesting that advanced donor age is not correlated with increased graft failure, although one study used age 44 as a cutoff for advanced age [15] and the other reported on experience with only 23 patients older than age 60 [16]. Regardless, the younger age of most living donors may limit the power to study this question.…”
Section: Recipient Outcomesmentioning
confidence: 86%